A Very Short Uranium(IV)–Rhodium(I) Bond with Net Double‐Dative Bonding Character. Issue 22 (27th April 2018) - Lu, Erli; Wooles, Ashley J.; Gregson, Matthew; Cobb, Philip J.; Liddle, Stephen T.
Abstract: Reaction of [U{C(SiMe3 )(PPh2 )}(BIPM)(μ‐Cl)Li(TMEDA)(μ‐TMEDA)0.5 ]2 (BIPM=C(PPh2 NSiMe3 )2 ; TMEDA=Me2 NCH2 CH2 NMe2 ) with [Rh(μ‐Cl)(COD)]2 (COD=cyclooctadiene) affords the heterotrimetallic U IV −Rh I 2 complex [U(Cl)2 {C(PPh2 NSiMe3 )(PPh[C6 H4 ]NSiMe3 )}{Rh(COD)}{Rh(CH(SiMe3 )(PPh2 )}]. This complex has a very short uranium–rhodium distance, the shortest uranium–rhodium bond on record and the shortest actinide–transition metal bond in terms of formal shortness ratio. Quantum‐chemical calculations reveal a remarkable Rh I → → U IV net double dative bond interaction, involving Rh I 4d z 2 ‐ and 4dxy/xz ‐type donation into vacant U IV 5f orbitals, resulting in a Wiberg/Nalewajski–Mrozek U−Rh bond order of 1.30/1.44, respectively. Despite being, formally, purely dative, the uranium–rhodium bonding interaction is the most substantial actinide–metal multiple bond yet prepared under conventional experimental conditions, as confirmed by structural, magnetic, and computational analyses. Abstract : Double dative : The shortest U−Rh bond distance on record and the shortest actinide–transition‐metal bond in terms of formal shortness ratio are presented. Surprisingly, quantum chemical calculations reveal a Rh I → → U IV net double dative bond interaction with a Nalewajski–Mrozek U−Rh bond order of 1.44.